Modelling Magnetorheological Dampers in Preyield and Postyield Regions - E. Palomares; A. L. Morales; A. J. Nieto; J. M. Chicharro; P. Pintado (Shock and Vibration)
The use of magnetorheological dampers has rapidly spread to many engineering applications, especially those related to transportation and civil engineering. The problem arises upon modelling their highly nonlinear behaviour: in spite of the huge number of apparently accurate models in the literature, most fail when considering the overall magnetomechanical behaviour. In this study, a brief but broad review of different magnetorheological damper models has been carried out, which includes characterisation, modelling, and comparison. Unlike many other studies, the analyses cover the behaviour from preyield to postyield regions of the MR fluid. The performance of the different models has been assessed by means of numerous experimental tests and by means of simulations in a simple and straightforward semiactive control case study. The results obtained prove that most models usually fail in predicting accurate low-velocity behaviour (before iron chains yield) and, as a result, may lead to bad estimations when used in control schemes due to modelling errors and chattering.